Analisis Manajemen Praktik Kerja Lapangan Terhadap Kompetensi Profesional Mahasiswa Program Studi Diploma Tiga Fisioterapi Universitas Widya Husada Semarang - Didik Purnomo; Suci Amanati (Excellent, 2026)
In the context of vocational physiotherapy education, Field Work Practice (internship) is a crucial element that serves to sharpen the professional skills of students. Organized internship management is projected to optimize clinical proficiency, ethical behavior, and the effectiveness of student interactions during physiotherapy service delivery. This research was conducted to evaluate the impact of internship management on the professional competence levels of students in the Diploma Three Physiotherapy Study Program at Widya Husada University, Semarang. This study adopted a quantitative methodology with a correlational design. The research subjects consisted of 43 respondents selected through a purposive sampling technique from a population of final-year students who had completed their internship period. The data collection instrument used was a Likert scale questionnaire to assess internship management variables and the professional capabilities of students. The data processing stages included validity, reliability, and normality testing, as well as correlation and simple linear regression analysis using SPSS software. Research findings confirm that internship management provides a significant positive contribution toward the improvement of students' professional competence (p < 0.05). High-quality internship management encompasses mature program planning, intensive clinical supervision, routine monitoring and evaluation, as well as strong synergy between the educational institution and the clinical practice site. It can be concluded that the quality of internship management is directly proportional to the level of professionalism possessed by prospective physiotherapists.